(De)compositions: Time and Technology in William Basinski’s The Disintegration Loops (2002) - Kemper, Jakko (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2019)
This paper analyzes William Basinski’s album The Disintegration Loops (2002) and argues that its aesthetic rendition of temporality and finitude is relevant in view of the relation between technology and the human perception of time for three reasons. First, the technological apparatus responsible for its creation mirrors the Derridean concepts of the spacing of time and autoimmunity. Second, the album’s affective appeal illustrates Martin Hägglund’s notion of chronolibido. Third, the music gives rise to a temporal media experience that exists at odds with the media experience afforded by what Mark B.N. Hansen has described as twenty-first-century media. Together, these three dimensions make The Disintegrations Loops an object that allows for an empirical grounding of the discussed theorizations of time and media.